Corrigendum to “Thieno[2,3-b]thiophene based polymers: Synthesis and optoelectronic properties” [Eur. Polym. J. 104 (2018) 72–80](S0014305718304725)(10.1016/j.eurpolymj.2018.05.001) - (:unkn) unknown (Elsevier Ltd, 2021)
The authors regret they missed to one of the authors, Mertcan Özel. The authorship now stands corrected in this corrigendum as above. The authors would like to apologise for any inconvenience caused. © 2021 Elsevier Ltd